Determinant factors of population services policy at the border of Indonesia - Posumah, Johnny Hanny; Pombengi, Jericho Danga (Management and Entrepreneurship: Trends of Development, 2022)
This study is aimed at identifying several problems while analyzing the determinants of population service policies in Lirung sub-district, Talaud archipelago district, North Sulawesi province, Indonesia. This study uses qualitative research methods, the data collection methods used in this study are as follows: interviews with employees and the people served, field observations, literature studies. Population services policy is optimal because it gets political support from the central government and local governments. Local governments often communicate to the public about population service policies. Resources for the implementation of policies and programs, policies and policy formats, and there need to be a real improvement, these factors have not been able to optimize service policies. This work has never been achieved and is the result of our research so that it can guarantee its authenticity. JEL Clasification: D78, I28, L88